MEDIA SOSIAL DAN LITERASI KEAGAMAAN GENERASI MILENIAL - Samsu Rizal; Ai Fatimah Nur Fuad (Prosiding Seminar Nasional Berseri, 2020)
This study aims to examine how the role of social media in millennial generation religious literacy. The rapid development of technology that has entered into human life has brought significant changes in the pattern of social livelihoods in the community. Social media has made the pattern of people’s behavior experience a shift in terms of culture, ethics and norms that exist. Indonesia with a large population with diverse ethnic, racial and religious cultures has a lot of potential for social change. From various groups and ages almost all Indonesian people use social media as a means to obtain and convey public information. This research is qualitative research. The research method used are observation, interviews and studies of literature relevant to the topic being studied. The results of this study indicate that social media for increasing or strengthening religious literacy can have both positive and negative impact; Positive because young generations are used to increase moderate religious literacy, but from the other side, it has a negative impact when teenagers use social media to access religious information that leads to things that are not moderate, exclusive and closed.